Cerium oxide thin films: synthesis, characterization, photocatalytic activity and influence on microbial growth. Issue 9 (21st October 2022) - Andronic, Luminita; Mamedov, Damir; Cazan, Cristina; Popa, Marcela; Chifiriuc, Mariana Carmen; Allaniyazov, Atabek; Palencsar, Simona; Karazhanov, Smagul Zh.
Abstract: The resistance of surfaces to biofouling remains a significant advantage for optical devices working in natural conditions, increasing their lifetime and reducing maintenance costs. This paper reports on the functionalities of transparent CeO2 thin films with thicknesses between 25 and 600 nm deposited by reactive magnetron sputtering on the glass substrate. The CeO2 photocatalytic performance exhibited an efficiency of 30% on imidacloprid degradation under 6 h of UV radiation and increased linearly with the irradiation time, suggesting a complete degradation within 48 h. The films did not alter the growth rate of the green algae Chlorella vulgaris after 72 h short-term exposure. The tested CeO2 films proved to efficiently inhibit with high efficiency the Staphylococcus aureus biofilms and planktonic growth (reducing the counts of bacterial cells by 2 to 8 logs), demonstrating the promising potential of these materials for obtaining antimicrobial and antibiofilm surfaces, with broad applications for the biomedical, ecological and industrial fields.